Pengaruh Perubahan Sanksi Hukum dalam Undang-Undang Tentang Ketentuan Umum dan Tata Cara Perpajakan Terhadap Penerimaan Pajak Penghasilan - Robby Alexander Sirait (Pusat Kajian Anggaran, 2022)
Tax reform in Indonesia began in 1983 with the enactment of Law Number 6 of 1983. One of the regulatory purposes of this law is to regulate tax sanctions in order to increase tax compliance and tax revenue. This study aims to determine the changes in tax sanctions from 1983 to 2009 and to examine the effect of tax sanctions on income tax revenues in Indonesia. By using a normative juridical approach, the results of the study show that the regulation of tax sanctions since the third amendment in 2007 is heavier than the previous amendments. Then, the results of quantitative research using the OLS method show that more serious tax sanctions have a positive and statistically significant effect on income tax revenues.